Independent and interdependent group contingencies to increase on‐task work behavior among adults with intellectual disabilities. - Daly, Svetlana; Phillips, Katrina J.; Mudford, Oliver C.; Sharp, Rebecca A. (Behavioral Interventions, 2024)
We applied independent and interdependent group contingencies in a counterbalanced reversal experimental design to the vocational on‐task behavior for two groups of adults with intellectual disabilities. On‐task behavior increased for all participants in both groups above a criterion of 80% of time on‐task during both treatment phases. Independent and interdependent group contingencies were equally effective in increasing on‐task behavior. Responding was maintained at the criterion level for all members of one group at a 4‐week follow‐up. No increases in negative social interactions were observed when the interdependent group contingency was in effect and participants reported both contingencies to be socially valid. We suggest that group contingencies can be an effective intervention in increasing on‐task behavior of individuals with intellectual disabilities in vocational settings.